2011
DOI: 10.1002/term.405
|View full text |Cite
|
Sign up to set email alerts
|

Dermal matrix scaffold engineered with adult mesenchymal stem cells and platelet-rich plasma as a potential tool for tissue repair and regeneration

Abstract: The purpose of this study was to investigate the efficacy of Integra®, an artificial dermal matrix used as a dermal template for skin regeneration, to form a multifunctional scaffold with human bone marrow‐derived mesenchymal stem cells (hMSCs) and platelet‐rich plasma (PRP) for tissue engineering and regenerative technology. First, we showed that PRP, used as a supplement for growth medium, represented an optimal substitute for animal serum as well as a source of multiple growth factors, was able to satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
(43 reference statements)
3
27
0
1
Order By: Relevance
“…Studies have shown that preconditioning by exposure to reduced levels of oxygen, incubation with nitric oxide, hydrogen peroxide or diazoxide, and treatment with pharmacological drugs, including phosphodiesterase inhibitors, angiotensin II receptor blocker and neuropeptide Y, may greatly enhance the therapeutic promise of BM-MSCs [44]. Moreover, it has been recently shown by our group that the treatment with platelet-derived rich plasma (PRP) [139], as well as irradiation with low level lasers [140], represent promising preconditioning approaches for stimulating BM-MSC proliferation, encompassing senescence during cell expansion and influencing stemness gene expression. Of interest, the genetic manipulation of MSC to overexpress cytokines and growth factors, such as HGF, VEGF and SDF-1, have also been proposed to improve neo-angiogenesis and the endogenous mechanisms of tissue repair/regeneration [44,141,142].…”
Section: Bone Marrow-derived Mesenchymal Stromal Cells (Bm-mscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that preconditioning by exposure to reduced levels of oxygen, incubation with nitric oxide, hydrogen peroxide or diazoxide, and treatment with pharmacological drugs, including phosphodiesterase inhibitors, angiotensin II receptor blocker and neuropeptide Y, may greatly enhance the therapeutic promise of BM-MSCs [44]. Moreover, it has been recently shown by our group that the treatment with platelet-derived rich plasma (PRP) [139], as well as irradiation with low level lasers [140], represent promising preconditioning approaches for stimulating BM-MSC proliferation, encompassing senescence during cell expansion and influencing stemness gene expression. Of interest, the genetic manipulation of MSC to overexpress cytokines and growth factors, such as HGF, VEGF and SDF-1, have also been proposed to improve neo-angiogenesis and the endogenous mechanisms of tissue repair/regeneration [44,141,142].…”
Section: Bone Marrow-derived Mesenchymal Stromal Cells (Bm-mscs)mentioning
confidence: 99%
“…Of interest, the genetic manipulation of MSC to overexpress cytokines and growth factors, such as HGF, VEGF and SDF-1, have also been proposed to improve neo-angiogenesis and the endogenous mechanisms of tissue repair/regeneration [44,141,142]. Finally, bioengineered three-dimensional matrices have been shown to represent appropriate devices to preserve the survival of the engrafted MSCs and assist their migration within the damaged tissues [139,143,144]. …”
Section: Bone Marrow-derived Mesenchymal Stromal Cells (Bm-mscs)mentioning
confidence: 99%
“…Currently, artificially synthesized inorganic materials (including hydroxyapatite and calcium phosphate) and polymer materials [including polylactic acid, polyglycolic acid (PGA), polyphophazenes and chitosan] may be used as scaffolds for bone tissue engineering (46). However, all of these materials have certain limitations in biocompatibility, biodegradability or mechanical matching (710). Therefore, additional research is required to investigate other types of composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, inclusion of WJ-MSC into Integra induced significant up-regulation of prototypical angiogenic and healing factors, stimulating pleiotropic aspects of neovascularization in experimental settings of angiogenesis, without altering the inflammatory response in the animals, thus demonstrating their potential benefit in therapeutic care of wounds and skin grafts [23]. Recently, Integra dermal matrix scaffold engineered with adult mesenchymal stem cells and platelet-rich plasma was investigated in vitro and demonstrated promising preliminary results [24].…”
Section: Integramentioning
confidence: 99%